Socio-pedagogical model in Higher Technician´s Nursing Training for prevention work - Rosangela Caicedo Quiroa; Julia Esther Céspedes Acuña; Rosa Ana Jaime Ojea (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction: The technician´s awareness of its social and community practice that contributes to a higher quality and affectionate attention to society is established in the profile of the Higher Technician´s Nursing Training. Objective: To propose a socio-pedagogical model in the Higher Technician´s Nursing Training for prevention work.  Material and methods:  A model proposal was made after a review of articles published in the database, and normative documents in the Ecuadorian context. Theoretical methods were applied for the comprehension, and explanation in the training of the Higher Technician in Nursing.   Development: A model is proposed, which socio-pedagogical intent is posed from the community perspective starting from a pedagogical direction, an epistemological approach, and logical systematization criteria of theory and practice, also considering the characteristics inherent to the sense of professional formation of the higher technician in nursing in the Bolivarian Technological Institute of Technology.  Conclusions: Community and school context, and community preventive service, built from a functional-structural systemic method with a qualitative approach were recognized as modeling subsystems. The model is a theoretical result of a project on doctoral programs in Pedagogical Sciences from the Cuba-Equator Agreement.  Keywords: socio-pedagogical model, prevention, systematization, community, school context.